Mingle Model for Teaching English Speaking Skill for College Students - darmayenti, Darmayenti; Nofiadri, Nofel (Institut Agama Islam Negeri Imam Bonjol Padang, 2015)
This paper is a report of a research and development project conducted in a speaking skill for the first-year students of State Institute for Islamic Studies Imam Bonjol Padang, academic year 2012/2013. Mingle as a technique in teaching speaking proposed by Pollard and Hess in 1997 was developed into a new model. Using ADDIE model as proposed by Dick and Carey in 1996, we collected the intended data through observation, questionnaire, and test. The result of the research showed that the implementation of model gave a significant difference in term of the students-learning outcome between the students who are taught through Mingle model and by traditional one or without Mingle model. The development of Mingle model included preparation, warming up, set the rule, act Mingle model, presentation, review and discussion. It is concluded that Mingle model is more effective to improve students on all components of speaking skill. Therefore, it is recommended that this model can be implemented at IAIN Imam Bonjol Padang.Â Copyright Â© 2015 by Al-Talim All right reserved